Excessive periostin expression and Th2 response in patients with nasal polyps: association with asthma - Wei, Yi (J Thorac Dis, 2018)
BACKGROUND: Periostin has been shown to be upregulated in chronic rhinosinusitis with nasal polyps (CRSwNP), especially in the CRSwNP patients with asthma. However, the underlying mechanism that how periostin contributes to the polyp genesis remains unclear. METHODS: In this study, we collected 63 CRSwNP patients’ nasal polyps (NPs) and 25 control subjects’ uncinated tissues. The expressions of periostin, thymic stromal lymphopoietin (TSLP), and other proinflammatory cytokines were examined using IHC staining, qRT-PCR, Western blot (WB), ELISA and FACS. The eosinophil infiltration, phenotype profiles and clinical characteristics of 2 NP subtypes (eosinophilic and non-eosinophilic) were evaluated. We examined the effects and mechanisms of periostin on human nasal epithelial cells cultured at air-liquid interface (ALI). RESULTS: The expressions of periostin in NPs with asthma were higher than without asthma and the control nasal mucosa and positively associated with the TSLP (P<0.05). And the periostin levels was positively associated with the basement membrane thickness, goblet cell hyperplasia and tissue eosinophilia polyp tissues, as well as the clinical parameters (computed tomography scores, polyp size, and polyp recurrence after endoscopic surgery). In vitro experiments show that type 2 T-helper (Th2) cytokines interleukin-4 (IL-4), IL-13 and TGF-β1 stimulates epithelial cells derived from polyp tissues to produce periostin through ERK and STAT6 signal pathways (P<0.05). Autocrine or recombinant periostin activates epithelial cells to produce TSLP via NF-κB signal pathways (P<0.05). The supernatant of periostin-treated epithelial cells activates dendritic cells (DCs), which subsequently induce naïve T cells to differentiate into Th2 cells and express IL-4 and IL-13. CONCLUSIONS: Our findings indicate periostin may play an important role in the polyp genesis, which can be considered as a therapeutic target for the management of CRSwNP.